Consumer perception & brand positioning of O'potato chips in particular reference to Akij food & beverage - Huque, Shariful hasanul (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2010.